Implantable Medical Device Website Efficacy in Informing Consumers Weighing Benefits/Risks of Health Care Options. (1st August 2016) - Wagner, Teresa; Lindstadt, Calandra; Jeon, Yongwoog; Mackert, Michael
Abstract : As more individuals turn to the Internet for health-related information and technology increases the availability and use of implantable medical devices (IMDs), the websites marketing these devices will increase. Healthy People 2020 mandates increased understandability and usability of health-related websites. This project used social cognitive theory (SCT) and health literacy constructs from the Institute of Medicine and National Institutes of Health to analyze eight IMD websites. Despite current recommendations, none of the websites considered for this study offered content of an appropriate reading level in conjunction with the United States average of eighth grade, and 75% of the sites failed to satisfy more than one health literacy construct. Most of the websites lacked many of the SCT constructs. More attention is needed to improve the usability of these and future IMD websites to simultaneously meet the goal of marketing IMDs and the Healthy People 2020 goals to educate patients and promote public health.